Molecular characterization of South African Ehrlichia ruminantium field isolates and development of a qPCR assay for the evaluation of a multivalent inactivated vaccine - Neves, Luís C.B.G. (University of Pretoria, 2024)
Thesis (PhD (Veterinary Tropical Diseases))--University of Pretoria, 2023.